Knowledge, attitude, and use of electronic cigarettes among Cairo University medical students - Ola A. Mostafa; Mahmoud A. Taha (SpringerOpen, 2024)
Abstract Background Electronic cigarette use has increased exponentially in Egypt and all over the world. However, there is insufficient information about their use among Cairo University medical students. This study aimed to assess e-cigarette knowledge, attitude, and use among Cairo University medical students. Methods A cross-sectional study of 300 consenting Cairo University medical students in the period of 1st November 2023 to 15th December 2023 was conducted using a self-administered questionnaire. A multistage sampling technique was used to randomly select 300 students: 150 students from the third year and 150 from the fifth year of the Cairo University Medical School. Results The mean age was 22.12 ± 1.87 years and 69.3% were males and 30.7% were females. Most of them (88.3%) had heard about e-cigarettes, with higher knowledge for students in their clinical years. The main sources of information were the media and friends (41.8% and 37.5%). By type, 14%, 12.7%, and 7.3% were cigarette, shisha, and e-cigarette smokers. Smoking prevalence was higher among males and students in their clinical years (12% and 4.7% in clinical and preclinical years respectively, p = 0.02). Among all, 39.3%, 10.2%, and 3.3% of the participants' friends, siblings, and parents smoked e-cigarettes respectively; compared to 16.7%, 17.9%, and 33% among the subset of participants who were e-cigarette smokers. A significantly lower percentage of e-cigarette smokers believed that e-cigarettes are addictive or cause respiratory problems, and a higher percentage thought that e-cigarettes are less harmful, help in smoking cessation, and that their nicotine content is lower than traditional cigarettes. Predictors of e-cigarette smoking were being in clinical years, cigarette and shisha smoking, and having friends who are e-cigarette smokers. Conclusion The study revealed several students' misconceptions and a wide variation in their attitudes about the harmful and addictive effects of e-cigarettes. This underscores the urgent need for the development of a medical school curriculum to provide accurate information about e-cigarettes to address the problem of its growing use in Egypt.